Energy constraint Bayesian compressive sensing detection algorithm - Chun-hui ZHAO; Yun-long XU (Tongxin xuebao)
To solve the shortage of nodes handling ability and limited energy in wireless sensor network,an energy constraint Bayesian compressive sensing detection algorithm was proposed.To balance the energy of the whole network and prevent network paralyzed due to too fast consumption of some nodes energy,the new algorithm not only considers effect of reconstruction,but also regards energy of nodes,while choosing observation vector，and uses improved clustering algorithm to select an optimal transmission path.The simulation results show that the energy constraint Bayesian compressive sensing detection algorithm has longer the survival time of the network than traditional Bayesian compressive sensing.